The uniform boundedness principle for order bounded operators - Charles Swartz (International Journal of Mathematics and Mathematical Sciences)
Under appropriate hypotheses on the spaces, it is shown that a sequence of order bounded linear operators which is pointwise order bounded is uniformly order bounded on order bounded subsets. This result is used to establish a Banach-Steinhaus Theorem for order bounded operators.